A SOCIOPRAGMATIC ANALYSIS OF THE DEVIATION OF POLITENESS PRINCIPLE IN THE USE OF TONTEMBOAN LANGUAGE IN MAKELA'I DIALECT: A CASE STUDY AMONG THE YOUTH OF TARAITAK SATU VILLAGE - Merari Teresa Oroh; Wimsje R. Palar; Nontje S. Pangemanan (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This study aims to answer two main problems. First, how do members of youth organizations in Taraitak Satu Village communicate through violations of the principles of linguistic politeness? Second, to what extent do young people in Taraitak Satu Village deviate from the principles of linguistic politeness in their social and professional interactions? This study uses a qualitative approach with free listening and listening (SBLC) as the main method of data collection, supported by note-taking as a secondary method. Data analysis refers to the referential approach based on the SPEAKING component of speech. The results revealed that youth in Taraitak Satu Village often use impolite language with intentions such as correcting, inciting, demeaning, mocking, ignoring, expelling, forcing, belittling, rejecting, and depriving others of their rights. These violations of language politeness norms include various aspects, such as tact, generosity, acceptance, humility, compatibility, and sympathy. The negative impact of these violations of linguistic politeness principles is not only felt by the youth individually, but also by their youth association groups. When words are delivered in a way that hurts the feelings of others, this can lead to controversy, hostility, dampen enthusiasm for group activities, and cause discord. This research is expected to contribute to efforts to preserve the Tontemboan language in the Makela'i dialect and provide a basis for strengthening the community to adhere to the principles of language politeness. Thus, this research is an important step to maintain the sustainability and quality of local languages in Taraitak Satu Village.